The contribution of ice algae to the winter energy budget of juvenile Antarctic krill in years with contrasting sea ice conditions. (18th October 2018) - Bernard, Kim S; Gunther, Lacey A; Mahaffey, Sean H; Qualls, Katelyn M; Sugla, Monisha; Saenz, Benjamin T; Cossio, Anthony M; Walsh, Jennifer; Reiss, Christian S
Abstract: Krill overwintering strategies vary with ontogeny and year; understanding this variability is essential to predicting how the species will respond to climate change in the future. Overwintering studies have focused on larval and adult krill, but we know little about how juvenile krill overwinter. The late winter diet of juvenile krill is important because it will determine their growth and development rates and consequently their reproductive potential the following spring. A diet rich in ice algae would promote growth and reproductive development. The Bransfield Strait (northern Antarctic Peninsula, AP) is an important overwintering ground for krill; it has been proposed this region offers a food-rich winter environment. We examined the contribution of ice algae to the energy budget of overwintering juvenile krill during 2 years with contrasting sea ice conditions. Grazing on ice algae contributed ∼146% to their winter energy budget in 2015, even though ice concentrations were ≤50% and consisted of newly formed pancake ice. However, when sea ice advanced late in the Bransfield Strait (2016), ice algae contributed significantly less (∼16%) to the winter energy budget of juvenile krill. Delayed sea ice advance may negatively affect growth and reproductive development of overwintering juvenile krill.